GIS for Education Working Group - the Education Commission (the Education Commission, 2021)
Keywords: _yl:a

Five ways geospatial analysis can help visualize and solve some of education’s biggest challenges - the Education Commission (the Education Commission, 2021)
As the education community continues to mobilize efforts towards achieving Sustainable Development Goal 4 (SDG 4), stakeholders at all levels of the system are grappling with questions on how to deliver inclusive quality education. What communities will benefit most...
Keywords: _yl:c

GIS for Education Working Group launches to promote data-driven decision-making - the Education Commission (the Education Commission, 2021)
Around the world, individuals are using maps to power everyday decisions: how do I navigate from my home to the nearest hospital? How many supermarkets are in my community? What public transportation is available for me to take to work?
Keywords: _yl:b

The Impact of GIS-Supported Teacher Allocation in Sierra Leone - EdTech Hub; Education Commission; Fab Inc. (EdTech Hub, 2022)
Keywords: HLR3; _r:AddedByZotZen

Commission Chair Gordon Brown’s keynote at the Education Disrupted, Education Reimagined WISE Summit - Education Commission (Education Commission, 2020)
It’s a real pleasure to speak to the WISE conference – to thank the Salzburg Global Seminar and WISE, particularly Sheikha Moza for organizing this, and to say that I thought that the initial remarks that we had from Asmaa and from Stavros were inspirational...

Transforming the Education Workforce: Learning teams for a learning generation - Education Commission (Education Commission, 2019)
The Education Commission's vision to strengthen, diversify, and transform the education workforce to deliver inclusive, quality education for all.
Keywords: C: International; ___working_potential_duplicate

The learning generation: investing in education for a changing world - The Education Commission (2016)

Universal Basic Education 2018 Indicator Profile for Basic Education Institutions in Nigeria: Public Schools Commission - Universal Basic Education Commission (2019)

Universal Basic Education Commission 2022 Annual Report - Universal Basic Education Commission (UBEC, 2022)

Digital Competency Development Manual: For teachers and educational personnel - Office of the Basic Education Commission (OBEC) (Government of Thailand, 2024)

AI User Manual: For teachers, students, schools, and parents in Thailand 2025 - Office of Academic Affairs and Educational Standards; Office of the Basic Education Commission (OBEC) (Government of Thailand, 2025)